Industry 4.0 Technologies and Digital Transition as enablers of Sustainability and Circular Economy practices: the case of Ornamental Stone sector - Duarte de Almeida, I.; da Silva, Agostinho (28th EurOMA Conference, 2021)
Sustainability awareness regarding natural resources depletion and social/environmental impacts of its extraction/transformation force companies to implement sustainable strategies. Our longitudinal case study addresses sustainability drivers/challenges to evaluate Circular Economy implementation success in the Portuguese Ornamental Stone sector. A movement to mobilize the POS sector to reduce waste and improve flexibility has thrived since 2004. Rocketed in 2011 with I4.0 technologies, boosted by R&D Projects, fostered by two Sustainable-Development-Goals (SDG9/SDG12), this mobilization creates smart technologies and new practices in an integrated approach to European-Competitiveness. Our findings match the EU’s integrated climate, energy policy and integrated approaches to natural resources sustainable management, protecting biodiversity and ecosystem services. (https://event.euroma2021.exordo.com/presentation/546/industry-40-technologies-and-amp-digital-transition-as-enablers-of-sustainability-and-amp-circular-economy-practices-the-case-of-ornamental-stone-sector)